TRANSFORMASI ORGANISASI MAHASISWA: PELATIHAN KEPEMIMPINAN, SOFT SKILLS, DAN STRATEGI LOLOS PROGRAM PENDANAAN DIKTI DI ORGANISASI MAHASISWA - Syaiputra Wahyuda Meisa Diningrat; Ahmad Zawawi; Dhian Gowinda Luh Safitri (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2026)
Most student organizations still face obstacles in carrying out their functions and achieving their goals, especially related to mastering leadership skills, soft skills, and funding strategies that are in accordance with the times. To answer this challenge, a training program was held that focused on building the capacity of members in a practical and sustainable manner, including leadership, soft skills development, and strategies for preparing DIKTI funding proposals. This program uses the ABCD (Asset-Based Community Development) approach with the stages of Discovery, Dream, Design, Define, and Destiny. Data collection was carried out by participatory observation, interviews, and pre-test and post-test questionnaire. Program outputs include training and mentoring services that strengthen leadership skills, communication, collaboration, conflict management, public speaking, time management, critical thinking, and technical skills in preparing DIKTI proposals. In addition, the training program also encourages socio-cultural transformation through strengthening collaboration, discipline, accountability, and member participation, so as to create a more productive and harmonious organizational culture. Supporting products in the form of training modules, draft proposals, work program charts, and evaluation instruments can be used as a reference for the development of other organizations. The results of the evaluation showed an improvement in the participants' abilities in all aspects assessed. Despite the obstacles related to the quality of human resources, time, and facilities, this program opens up opportunities for student organizations to be more competitive, structured, and adaptive.